On the issue of genesis of the traditional dwelling of Turkic peoples - Ibrayeva Г.О. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article attempts to illuminate culturologically the theoretical and methodological genesis issues of Turkic traditional dwelling within the framework of historical ethnology through the value content of culture, which is the basis of self-organisation of any ethnos. The article contains a brief descriptions of the cultural code of traditional Turkic mobile dwellings on the basis of comparative-cultural analysis of open historical data obtained as a result of archaeological and ethnographic studies of different times with the aim to find common semantic elements of a unified cultural code. The traditional mobile dwelling of the ancient autochthonous inhabitants of the Great Steppe and the Kazakh people - kiiz uy, one of the modern representatives of the Turkic ethnos, whose common proto-Turkic ethno- and glottogenesis, historical zone of habitation and cultural-historical community were connected with the vast area of the Eurasian steppes, was chosen as an analogue.